1998
DOI: 10.1103/physrevb.58.4846
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects in a one-dimensional constriction

Abstract: We have investigated the transport properties of one-dimensional (1D) constrictions defined by split-gates in high quality GaAs/AlGaAs heterostructures. In addition to the usual quantized conductance plateaus, the equilibrium conductance shows a structure close to 0.7(2e 2 /h), and in consolidating our previous work [K. J. Thomas et al., Phys. Rev. Lett. 77, 135 (1996)] this 0.7 structure has been investigated in a wide range of samples as a function of temperature, carrier density, in-plane magnetic field B a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
351
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(383 citation statements)
references
References 45 publications
27
351
4
1
Order By: Relevance
“…At temperatures around 1K, measured linear conductance curves of most clean QPCs show a pronounced shoulder at around 0.7G Q , as shown in figure 2.5 a green line, and in figure 1.2 a (see also Thomas et al, 1998). This shoulder gradually weakens if temperature is lowered.…”
Section: Temperature Dependencementioning
confidence: 80%
“…At temperatures around 1K, measured linear conductance curves of most clean QPCs show a pronounced shoulder at around 0.7G Q , as shown in figure 2.5 a green line, and in figure 1.2 a (see also Thomas et al, 1998). This shoulder gradually weakens if temperature is lowered.…”
Section: Temperature Dependencementioning
confidence: 80%
“…Our new findings also provide an explanation for one of the most characteristic features of the 0.7 Structure, which has, to our knowledge, not been explained by any model or theory so far -the question of how the 0.7 Structure can survive to such high temperatures, when all other conductance features have disappeared [4].…”
mentioning
confidence: 80%
“…Using DC-bias spectroscopy [3], we show that as spin-down (lower energy) subbands begin to populate, they abruptly drop in energy by as much as 0.5 meV, within a vanishingly small range of gate-voltage. These results also cast doubt on basic assumptions which are often made when analysing quantum-wires -such as the idea that electron density is proportional or equivalent to gate-voltage, and the validity of an 'exchange-enhanced g-factor' in quantum wires [4].Our new findings also provide an explanation for one of the most characteristic features of the 0.7 Structure, which has, to our knowledge, not been explained by any model or theory so far -the question of how the 0.7 Structure can survive to such high temperatures, when all other conductance features have disappeared [4].Our samples consist of split-gate devices [5] defined by electron-beam lithography on a Hall bar etched from a GaAs/Al x Ga 1−x As heterostructure. All the samples used in this work have a length of 0.4 µm and a width of 0.7 µm.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…• Thomas et al [8] originally identified an anomalous structure in low-temperature conductance below the first quantized step in GaAs QPCs at about G 0.7 0 . It has been argued that this perceived anomaly is an intrinsic property caused by some many-body effect independent of the details of the material system.…”
Section: Introductionmentioning
confidence: 99%